2016
DOI: 10.1155/2016/1948029
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis for Rolling Bearing under Variable Conditions Based on Image Recognition

Abstract: Rolling bearing faults often lead to electromechanical system failure due to its high speed and complex working conditions. Recently, a large amount of fault diagnosis studies for rolling bearing based on vibration data has been reported. However, few studies have focused on fault diagnosis for rolling bearings under variable conditions. This paper proposes a fault diagnosis method based on image recognition for rolling bearings to realize fault classification under variable working conditions. The proposed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…6. The 2D time-frequency matrix of signal is reconstructed by formula (9) and then the noise is suppressed by applying the generalized S inverse transformation.…”
Section: Based On Singular Value Sequences Subsetsmentioning
confidence: 99%
See 2 more Smart Citations
“…6. The 2D time-frequency matrix of signal is reconstructed by formula (9) and then the noise is suppressed by applying the generalized S inverse transformation.…”
Section: Based On Singular Value Sequences Subsetsmentioning
confidence: 99%
“…Image is an important form of fault diagnosis information, including the application of Charge Coupled Device(CCD) acquired image, spectral image and sound image. 810…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the capability of classification model has a significant influence on diagnostic results, indicating the need to attempt appropriate pattern recognition algorithm for rotating machinery (Han and Jiang, 2016). The most used classifiers in this field are artificial neural networks (ANNs) including back propagation neural network (BPNN), radical basis function (RBF), learning vector quantization (LVQ) (Jiang and Liu, 2011), wavelet neural network (WNN) (Lei et al, 2011), extreme learning machine (ELM) (Tian et al, 2015), probabilistic neural network (PNN) (Zhou and Cheng, 2016; Dou and Zhou, 2016) and so forth, and support vector machine (SVM) (Li and Zhang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sanz et al [2] presented a method for detecting the states of rotating machinery with vibration analysis. Zhou and Cheng [3] proposed a fault diagnosis method based on image recognition for rolling bearing to realize fault classification under variable working conditions. Li et al [4] presented a model for deep statistical feature learning from vibration measurements of rotating machinery, and the results showed that deep learning with statistical feature extraction has an essential improvement potential for diagnosing rotating machinery faults.…”
Section: Introductionmentioning
confidence: 99%